1976
DOI: 10.1159/000152837
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphs of the Inhabitants of the Island of Hvar, Yugoslavia

Abstract: An analysis of the digito-palmar dermatoglyphs obtained from 231 inhabitants of the Island of Hvar, divided into two groups according to some sociocultural differences, is presented. The quantitative features do not reveal heterogeneity between the groups, while some qualitative palmar dermatoglyphic features are statistically significantly different. The results are discussed in the light of the possible influence of some different evolutionary processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
3
6
0
Order By: Relevance
“…It is also compatible with the recent demography (Rudan et al, 198213;Jovanovic et al, 1984) and linguistic characteristics of the inhabitants of the island (Sujoldzic et al, 1983(Sujoldzic et al, ,1984(Sujoldzic et al, -1985. It parallels the findings of Rudan (1972Rudan ( ,1975aRudan ( ,b, 1977Rudan ( ,1982 and Rudan and Schmutzer (1976) …”
Section: Discussionsupporting
confidence: 88%
“…It is also compatible with the recent demography (Rudan et al, 198213;Jovanovic et al, 1984) and linguistic characteristics of the inhabitants of the island (Sujoldzic et al, 1983(Sujoldzic et al, ,1984(Sujoldzic et al, -1985. It parallels the findings of Rudan (1972Rudan ( ,1975aRudan ( ,b, 1977Rudan ( ,1982 and Rudan and Schmutzer (1976) …”
Section: Discussionsupporting
confidence: 88%
“…The subpopulation of Barbat is probably different because of a high migration rate from the mainland during the past centuries. These results are similar as it was found in these from earlier researches on the other Croatian islands: Hvar (Rudan and Schmutzer, 1976), Koreula (Mili6ic, 1985-86, 1987, Brad (Milidid, 1994(Milidid, , 2000 where subpopulations of the eastern parts of islands, closest to the migration ways from the mainland differ the most from the western subpopulations in qualitative dermatoglyphics traits.…”
Section: Discussionsupporting
confidence: 91%
“…Chai [1972] has also found that, for example, anthropometric dimen sions are subject to a more rapid diversifica tion than dermatoglyphic features. Our in vestigations have also confirmed that the process of diversification produces different effects on the quantitative and qualitative dermatoglyphic traits [Rudan and Schmutzer, 1976]. Therefore, it should be pointed out that the results of this study show that some biological characteristics go through more rapid changes while others, though perhaps functionally more significant for the organism (i.e., blood pressure, lung func tion, etc.…”
Section: Resultssupporting
confidence: 79%